Advanced protein formulations. (1st May 2015) - Wang, Wei
Abstract: It is well recognized that protein product development is far more challenging than that for small‐molecule drugs. The major challenges include inherent sensitivity to different types of stresses during the drug product manufacturing process, high rate of physical and chemical degradation during long‐term storage, and enhanced aggregation and/or viscosity at high protein concentrations. In the past decade, many novel formulation concepts and technologies have been or are being developed to address these product development challenges for proteins. These concepts and technologies include use of uncommon/combination of formulation stabilizers, conjugation or fusion with potential stabilizers, site‐specific mutagenesis, and preparation of nontraditional types of dosage forms—semiaqueous solutions, nonfreeze‐dried solid formulations, suspensions, and other emerging concepts. No one technology appears to be mature, ideal, and/or adequate to address all the challenges. These gaps will likely remain in the foreseeable future and need significant efforts for ultimate resolution.